Design and development of lead-free glass-metallic vacuum materials for the construction and thermal performance of smart fusion edge-sealed vacuum glazing - Saim Memon; Philip Eames (2020)
Advancement in hermetic (vacuum-tight) edge-sealing materials has been one of the challenges since decades because of the existing cost, use of hazardous substance and complexity-to-construct issues in vacuum glazing. This paper presents novel experimental findings with designs and methods developed to construct and analyse thermal performance of the fusion edge-sealed vacuum glazing. The novel concept of fusion edge-seal consists of forming a thin glass-metallic rigid textured layer, in which the formation processes and experimental glass-metallic textured surface bonding property tests of 15 samples are microstructurally analysed using FIB-SEM and optical microscopy and succeeded the correct mixture of B2O338-Sn62 wt%. Experimental analyses of at least 60 samples conducted using different techniques and Pb-free materials, among which five vacuum glazing samples of various designs and techniques discussed in this paper. The fusion edge-sealed vacuum glazing, constructed with bonded Sn62-B2O338 wt% surface textured fused with Sn90-In10 wt% alloy at 450 °C, achieved at the hot-plate surface heat induction of 50 ± 5 °C and the cavity vacuum pressure of 8.2 · 10−4 Pa. Validated 3D FEM employed and the centre-of-sheet and total thermal transmittance values of fusion edge-sealed vacuum glazing (sample ‘A5’), area of 300 · 8300 mm with 10 mm wide fusion edge-seal, predicted to be 1.039 and 1.4038 Wm−2K−1, respectively.